Eye-Robo graphical programming interface for the EYE-C microcontroller - Bollozos, Lucille T. (2011)
The project aimed to develop a graphical programming interface for the EYE-C microcontroller robot. The interface provided an easier way to program the EYE-C microcontroller. As a consequence, debugging was also easier. As a further help, Eye-Robo was linked to the RobotBASIC simulator. This tool can be utilized to help generate interest in science and technology and at the same time serve as an introduction to programming concepts.